2021
DOI: 10.3389/fmicb.2021.619141
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbial Composition Is Species-Specific and Individual-Specific in Two Species of Estrildid Finches, the Bengalese Finch and the Zebra Finch

Abstract: Microbial communities residing in the gastrointestinal tracts of animals have profound impacts on the physiological processes of their hosts. In humans, host-specific and environmental factors likely interact together to shape gut microbial communities, resulting in remarkable inter-individual differences. However, we still lack a full understanding of to what extent microbes are individual-specific and controlled by host-specific factors across different animal taxa. Here, we document the gut microbial charac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 125 publications
(144 reference statements)
2
17
1
Order By: Relevance
“…In our study, the gut microbiota of three wild bird species were found to mainly comprise six phyla, including Firmicutes, Proteobacteria, Fusobacteria, Actinobacteria, Bacteroidetes, and Campilobacterota, consistent with studies on other birds, such as the Greylag Geese (Anser anser; Wang et al, 2018), Bengalese Finch (Lonchura striata domestica) and Zebra Finch (Taeniopygia guttata; Maraci et al, 2021), Hooded Crane (Grus monacha; Fu et al, 2020), and Whooper Swan (Cygnus cygnus; Wang et al, 2021). Firmicutes, the most dominant species among the three hosts, generally dominate the gut microbiota in all animals and play an important role in maintaining gut homeostasis and assisting digestion.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the gut microbiota of three wild bird species were found to mainly comprise six phyla, including Firmicutes, Proteobacteria, Fusobacteria, Actinobacteria, Bacteroidetes, and Campilobacterota, consistent with studies on other birds, such as the Greylag Geese (Anser anser; Wang et al, 2018), Bengalese Finch (Lonchura striata domestica) and Zebra Finch (Taeniopygia guttata; Maraci et al, 2021), Hooded Crane (Grus monacha; Fu et al, 2020), and Whooper Swan (Cygnus cygnus; Wang et al, 2021). Firmicutes, the most dominant species among the three hosts, generally dominate the gut microbiota in all animals and play an important role in maintaining gut homeostasis and assisting digestion.…”
Section: Discussionsupporting
confidence: 90%
“…At the phylum level of the cecum, the Campilobacterota phyla were greatly improved with 3% HILM supplementation, which was not a usual report with the phylum by poultry studies under natural or captivity conditions. Although some members of this phylum might cause diseases in wild and domestic animals, they were considered to be nonpathogenic and were frequently isolated from healthy birds ( Zhao Y. et al, 2019 ; Chen et al, 2020 ; Maraci et al, 2021 ). It was showed that HILM could affect intestinal microbiota, either directly or indirectly, by modulating jejunal and cecal microbial compositions at the phylum level, especially a diet with 3% HILM supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the microbial analysis are described in Maraci et al 61 . In short, microbial DNA was extracted using the QIAamp PowerFecal DNA Kit (Qiagen), as described in the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%